2006
DOI: 10.4319/lo.2006.51.1_part_2.0558
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation and dissimilatory nitrate reduction to ammonium (DNRA) support nitrogen dynamics in Texas estuaries

Abstract: We conducted continuous-flow experiments on intact sediment cores from Laguna Madre, Sabine Lake, East Matagorda Bay, and Nueces Estuary to evaluate internal nitrogen (N) sources, sinks, and retention mechanisms in Texas estuaries having different salinities. Mean ammonium (NH ) flux ranged from slight uptake (negative values) Nitrogen (N), a key nutrient limiting primary production in coastal ecosystems, can be introduced to coastal waters via tributaries, atmospheric deposition, or groundwater inputs as nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
171
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 272 publications
(193 citation statements)
references
References 40 publications
12
171
2
1
Order By: Relevance
“…We found a small, statistically insignificant 17 decrease in ammonium fluxes with increasing salinity. To account for differences in 18 sediment type, nutrient loading and organic matter supply to the sediment between these 19 systems, we also compared the ratio of ammonium efflux to total nitrogen flux and found 20 an increase with increasing salinities, in agreement with the results from Texas estuaries 21 (Gardner et al 2006). However, the differences in median are not statistically significant, 22 hence, no general conclusions about the relationship between ammonium fluxes and 1 salinity can be drawn.…”
supporting
confidence: 74%
“…We found a small, statistically insignificant 17 decrease in ammonium fluxes with increasing salinity. To account for differences in 18 sediment type, nutrient loading and organic matter supply to the sediment between these 19 systems, we also compared the ratio of ammonium efflux to total nitrogen flux and found 20 an increase with increasing salinities, in agreement with the results from Texas estuaries 21 (Gardner et al 2006). However, the differences in median are not statistically significant, 22 hence, no general conclusions about the relationship between ammonium fluxes and 1 salinity can be drawn.…”
supporting
confidence: 74%
“…DNRA is favored in organic rich-low NO 3 -systems (Burgin and Hamilton 2007). This process has been reported in fresh water sediments but has mostly been considered a minor pathway for NO 3 -removal (Gardner et al 2006;Erler et al 2008). To the best of our knowledge, DNRA has not been investigated in the SJR and Zamora et al (2012) suggested anaerobic mineralization is a key process for explaining high NH 4 ?…”
Section: Discussionmentioning
confidence: 99%
“…Continuous flow experiments with intact sediment cores were used to determine the fluxes of nutrients and dissolved gases (Lavrentyev et al 2000, Gardner et al 2006, McCarthy et al 2007. Three intact sediment cores (6.4 cm diameter and approx 17 cm high) and overlying water (;400 ml per core) were collected by hand from each habitat two hours prior to low tide in February, May, July, and October of 2007.…”
Section: Sediment N Fluxes and N Transformationsmentioning
confidence: 99%